The impact of proactive behavior on entrepreneurial alertness and dynamic capabilities - Ahmed Mousa Mahmood; Moataz Ibrahim Qinbr; Faiez Thanoon Jassem; Yurii Khlaponin (Encuentros)
Entrepreneurship is identifying and capitalizing on novel possibilities, and possessing a sharp entrepreneurial acumen is crucial for identifying and exploiting these prospects.  The article examines the intricate relationship between proactive conduct, entrepreneurial awareness, and organizational dynamism. The research investigates the influence of proactive conduct on entrepreneurial awareness and the development and use of dynamic skills in entrepreneurial environments.This study investigates proactive behavior, entrepreneurial awareness, and company dynamism via a comprehensive survey of existing literature.The study shows that dynamic capabilities are crucial in connecting proactive behavior with entrepreneurial awareness. The research asserts that the company's capacity to generate and use dynamic capabilities is crucial in enhancing proactive behavior, entrepreneurial awareness, and dynamism.